Desinfecção de água por radiação solar no município de Santarém - VASCONCELOS, Alessandro Santos de (Universidade Federal do Oeste do Pará, 2024)
Water is an essential element for the maintenance of life and we depend on it to survive, either directly or indirectly. One of the concerns of water and health regulatory bodies is about the quality of water for human consumption and its various uses that according to the WHO (World Health Organization) about 60% of the world population receives water with quality outside the established standards. Because of this, several disinfection strategies have been tested for the treatment of water, so that it has an adequate quality for consumption, however, many of these disinfection processes have their high cost, with this, few people have access. The objective of this work was to evaluate the efficiency of water disinfection by means of solar radiation using a solar collector with low cost materials and easy access. Environmental water was used for disinfection, collected directly from the Tapajós River with pH and temperature measurement. The disinfection test was carried out in Santarém, western region of the State of Pará, on the premises of the Universidade Federal do Oeste do Pará (UFOPA), the experiments were carried out on a sunny day, starting around 10:00 am until 4:00 pm: 00 hours, the local temperature was between 30° and 32°C. Environmental water was collected in sterilized plastic containers, then transferred to the reservoir so that the disinfection process could begin. During the experiment, 4 collections were made, one of the water at ambient conditions (32 °C) and the others at different temperatures (40 °C, 45 °C and 49 °C). After the microbiological analysis, it was observed that the best temperature was 40 ºC, presenting the lowest count of heterotrophic bacteria, leaving the water in the microbiological standard that is established by Ordinance No. disinfection is technically feasible, as microbial inactivation occurs.